The Impact of Chronic Limb-Threatening Ischemia on Cardiac Surgery - Wakabayashi, Naohiro; Kikuchi, Shinsuke; Kuriyama, Naoya; Kikuchi, Yuta; Tsutsui, Masahiro; Ise, Hayato; Yoshida, Yuri; Uchida, Daiki; Koya, Atsuhiro; Shirasaka, Tomonori; Azuma, Nobuyoshi; Kamiya, Hiroyuki (Frontiers in Surgery, 2022)
Purpose: The effect of chronic limb threatening ischemia (CLTI) on advanced cardiac disease, which requires surgical treatment, has rarely been reported. The purpose of this study was to review the outcomes of cardiac surgery in patients with CLTI and determine the risk factors, with a particular focus on the severity of CLTI. Patients: The baseline characteristics and outcomes of 33 patients who were treated for CLTI and underwent cardiac surgery were retrospectively analyzed. The states of CLTI were evaluated based on the Wound, Ischemia, and foot Infection (WIfI) classification system, and 33 patients were divided into the low-WIfI group (stages 1–2, n=13) and high-WIfI group (stages 3–4, n=20). Results: The in-hospital mortality rate was 0% in low-WIfI group and 35% in high-WIfI group (p=0.027). Postoperative complications, particularly severe infections, occurred more frequently among high-WIfI group than low-WIfI group (70.0% vs. 23.1%, p < 0.01). Multivariable analysis identified foot infection grade as a WIfI classification factor and lower albumin levels as factors significantly associated with postoperative complications. The 1-year and 2-year survival rates were 84.6% and 67.7% in low-WIfI group and 45% and 28.1% in high-WIfI group, respectively (p=0.011). Conclusions: Cardiac surgery in patients with high WIfI stage was an extremely high-risk procedure. In such patients, lowering the WIfI stage by lower extremity revascularization and/or debridement of diseased parts prior to cardiac surgery can be considered.